1974
DOI: 10.5254/1.3540470
|View full text |Cite
|
Sign up to set email alerts
|

New Studies of Carbon—Rubber Gel

Abstract: High resolution electron micrographs of undistorted carbon—rubber gel were obtained by ultramicrotomy of frozen unvulcanized SBR compounds which were subsequently extracted with benzene to remove any soluble rubber. The remaining black and rubber form a 3-dimensional, meshlike network which is larger than the size of primary units of the black itself. The networks for different blacks indicate considerable compaction which increases in the direction of lower structure and surface activity (e.g., normal vs. gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Three peaks were observed in both spectra. These peaks could be assigned to silicon atoms with geminal silanol Q 2 , single silanol Q 3 , and siloxane bridge Q 4 15 ( Table 2). As seen, the relative intensities of Q 2 , Q 3 , and Q 4 for the precipitated silica were quite similar to those for the fumed silica.…”
Section: Resultsmentioning
confidence: 99%
“…Three peaks were observed in both spectra. These peaks could be assigned to silicon atoms with geminal silanol Q 2 , single silanol Q 3 , and siloxane bridge Q 4 15 ( Table 2). As seen, the relative intensities of Q 2 , Q 3 , and Q 4 for the precipitated silica were quite similar to those for the fumed silica.…”
Section: Resultsmentioning
confidence: 99%
“…A third region of unbound and mobile rubber interpenetrates the three-dimensional soft network. Figure 1 is a representation of this complex structure, which was somewhat obvious in micrographs published around 24 years ago, 6 the details of which can be inferred from NMR measurements. 7 By modeling an optimum dispersion of carbon black particles as a face-centered cubic pattern, we calculated that the mean length of "connecting filaments" should be in the 25-50 nm range, an interesting result to be compared with the mean random coil diameter of a high molecular weight polymer (i.e., 50 nm).…”
Section: Morphology Of Uncured Filled Rubber Compoundsmentioning
confidence: 99%
“…Bound rubber is found to depend on silica level according to eq. (4), provided that one takes into account the volume fraction of the silane, i.e., ͓%BdR͔ ϭ A ϫ 2.5 ϫ ⌽ siϩsil ϩ B ϫ 14.1 ϫ ⌽ SiϩSil 2 (6) Accordingly, the curve in Figure 10 is drawn using A ϭ 0.1 and B ϭ 65. The good fit obtained confirms that the silane covers the silica particles well and bound rubber occurs because of chemical bonding.…”
Section: Bound Rubber In Silica-filled Compoundsmentioning
confidence: 99%
“…In case of high structured and high surface area carbon blacks like SAF and HAF, Ban et al 17 demonstrated the existence of physical adsorption that results in BdR formation. Dannenberg 18 showed a decrease in BdR per unit surface with decreasing particle size of carbon blacks for styrenebutadiene rubber (SBR) compounds filled with 50 phr of carbon black.…”
Section: Effect Of Types Of Carbon Blackmentioning
confidence: 99%